The Stages of Formation and Development of Genetics at the Kazan University - A.I. Ermolaev (Учёные записки Казанского университета: Серия Естественные науки)
The paper outlines the stages of development of genetic studies at the Kazan University (KU), from 1913 to the late 20th century. At the first stage (the 1913s–1920s), the study of genetic problems is associated with the names of V.I. Smirnov (botanist), N.A. Livanov (zoologist), V.S. Gruzdev and T.I. Yudin (physicians). The second stage, the peak in the development of classical genetics at the KU, is associated with the name of V.N. Slepkov and his genetic laboratory. Unfortunately, the entire “Slepkov's School” perished in the years of repression. The third stage is the years of Lysenkoism. However, the first department of genetics appeared at the KU (headed by M.G. Stekol'shchikov, Associate Professor) in these years and existed from 1948 to 1953. The fourth stage, the revival of genetic research (the early 1960s – 1976), is associated with the names of M.I. Belyaeva, M.G. Stekol'shchikov, and B.I. Barabanshchikov. The fifth stage is the first 25 years of the existence of the Department of Genetics at the KU (from 1976 to the late 20th century) headed by B.I. Barabanshchikov, Professor. The modern sixth stage (the 21st century) has not been considered as it has not yet become history. The paper is based on many archival materials, some of which have been for the first time introduced into scientific circulation.